KENDALA DAN PERMASALAHAN PEMBERLAKUAN UU NO. 23 TAHUN 2011 TENTANG ABSTRAK PENGELOLAAN ZAKAT: - Arif Gunawan Santoso (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
Policy implementation remains one of the most common problems in developing countries due to the some strategic or administrative constrains. This study employs quantitative approach by using theory of public policy as the analytic lens. The research findings reveal that there are some problems and constraints in the policy implementation related to ZIS (zakât, infaq, cadaqât) i.e. Law No. 23 Year 2011 about zakât management. This study portrays a zakât institution in Surabaya, East Java. The readiness of policy operator, namely MoRA and BAZNAS becomes the dominant factor which hinders the implementation of zakât management policy. In addition, the legal problem due to the filing of Law No. 23/2011 to the Constitutional Court by KOMAZ also contributed significantly to the implementation of this Law.